Special glue for anti-falling and anti-deformation rock board containing high carbon fiber
By adding high-carbon fibers and specific modifiers to special glue for rock slabs, the problems of unbalanced performance and insufficient stability of existing glue products are solved, and more efficient performance coordination and stability improvement are achieved.
Patent Information
- Application Number
- CN202411610983.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-11-12
AI Technical Summary
The mechanical properties and thermal conductivity of existing special glues for rock slabs are difficult to balance and coordinate, and their resistance to cold and heat, acid and corrosion resistance are poor, which limits the efficiency of the product.
Special glue for anti-falling and anti-deforming rock slabs containing high carbon fiber is used to coordinate the performance of glue products through the combination of quartz sand, cement, polymer glue powder, hydroxypropyl methyl cellulose, carbon fiber hybridization-based mixing agent and metakaolin modifier.
The impact toughness, tensile strength and thermal conductivity of glue products have been improved, and the product's resistance to heat, acid, corrosion and solvent resistance is significantly improved.
Smart Images

Figure BDA0005130890600000111 
Figure BDA0005130890600000121 
Figure BDA0005130890600000131
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of special adhesives for rock slabs, and in particular to a special adhesive for rock slabs containing high carbon fibers and capable of preventing them from falling off and deforming. Background Art
[0002] The rock slab is made of natural raw materials through a special process, with the help of a press with a capacity of more than 10,000 tons, and fired at high temperature. It can be cut, drilled, polished and other processing processes. It is a new type of ceramic material with super-large specifications. The special glue for rock slabs needs to be suitable for the paving of large-sized rock slabs. The existing special glue for rock slabs has poor mechanical properties. At the same time, the mechanical properties and thermal conductivity of the product are difficult to balance and improve. The product has poor resistance to cold and heat, acid corrosion and solvents, which limits the use efficiency of the product. Based on this, the present invention further improves it. Summary of the invention
[0003] In view of the defects of the prior art, the purpose of the present invention is to provide a special adhesive for anti-falling and anti-deformation rock slabs containing high carbon fiber, so as to solve the problems raised in the above background technology.
[0004] The present invention solves the technical problem by adopting the following technical solution:
[0005] The present invention provides a special adhesive for anti-falling and anti-deformation rock plates containing high carbon fiber, comprising the following raw materials in parts by weight:
[0006] 60-70 parts of quartz sand, 30-35 parts of cement, 10-15 parts of carbon fiber hybridization-based conditioning agent, 5-8 parts of polymer rubber powder, 3-5 parts of hydroxypropyl methylcellulose, 4-7 parts of metakaolin modifier and 40-45 parts of water;
[0007] The preparation method of the special glue for rock slabs is as follows: weigh the above raw materials in parts by weight according to the ratio, and then mix the raw materials sufficiently to obtain the special glue for rock slabs of the present invention.
[0008] Preferably, the special glue for preventing falling off and deformation of rock slabs comprises the following raw materials in parts by weight:
[0009] 65 parts of quartz sand, 32.5 parts of cement, 12.5 parts of carbon fiber hybrid-based conditioning agent, 6.5 parts of polymer rubber powder, 4 parts of hydroxypropyl methylcellulose, 5.5 parts of kaolin modifier and 42.5 parts of water.
[0010] Preferably, the polymer powder is acrylic powder; the specification of quartz sand is 200 mesh; and the cement is silicate 42.5R cement.
[0011] Preferably, the preparation method of the carbon fiber hybrid-based feed agent is:
[0012] S01: first prepare a lanthanum chloride solution with a mass fraction of 2-5%, and then place silicon carbide in a lanthanum chloride solution with a mass fraction of 2-5% that is 3-5 times the total amount of silicon carbide, and stir and mix thoroughly to obtain silicon carbide liquid;
[0013] S02: 3 to 5 parts of bauxite, 1 to 3 parts of nano-silica sol and 2 to 4 parts of sodium citrate solution are mixed to obtain a bauxite agent;
[0014] S03: 5 to 8 parts of silicon carbide liquid and 2 to 4 parts of bauxite agent are mixed and ultrasonically treated. After the ultrasonic treatment is completed, the mixture is filtered and dried; heat treated at 150 to 160° C. for 10 to 15 minutes, and then air-cooled to room temperature to obtain a silicon carbide-bauxite body;
[0015] S04: The silicon carbide-bauxite body and the carbon fiber hybrid liquid are mixed in a weight ratio of 5:3 and ball-milled at a ball milling speed of 1000 r / min for 2 hours. After the ball milling is completed, the mixture is filtered and dried to obtain a carbon fiber hybrid-based adjusting agent.
[0016] Preferably, the mass fraction of the sodium citrate solution is 6-8%; the ultrasonic power of the blending ultrasonic treatment is 350-400W, and the ultrasonic time is 20-30min.
[0017] Preferably, the carbon fiber hybrid liquid comprises the following raw materials in parts by weight:
[0018] 5 to 8 parts of carbon fiber, 2 to 3 parts of cerium oxide, 1 to 2 parts of stearic acid, 2 to 4 parts of nano zirconium oxide and 8 to 12 parts of sodium dodecylbenzene sulfonate solution.
[0019] Preferably, the mass fraction of the sodium dodecylbenzene sulfonate solution is 3-5%.
[0020] Preferably, the preparation method of the metakaolin modifier is:
[0021] S11: mixing nano zinc oxide and nano silicon nitride in a weight ratio of 3:2, and then calcining at 230-240° C. for 1-2 hours. After the calcination is completed, cooling to room temperature is performed to obtain a calcined material;
[0022] Then, the calcined material is added into a potassium permanganate solution which is 4 to 7 times the total amount of the calcined material, stirred and mixed thoroughly, and then washed with water, filtered and dried to obtain a nano composite additive;
[0023] S12: adding 3 to 5 parts of silane coupling agent KH550 and 1 to 3 parts of dopamine hydrochloride solution to 5 to 8 parts of ethanol solvent, and then adding 2 to 4 parts of nanocomposite additives and stirring to obtain a coupling compound solution;
[0024] S13: stirring and modifying the metakaolin and the coupling compound liquid in a weight ratio of 2:5, filtering and drying after the stirring is completed to obtain a metakaolin modifier.
[0025] Preferably, the mass fraction of the dopamine hydrochloride solution is 5-8%; the mass fraction of the potassium permanganate solution is 3-6%.
[0026] Preferably, the stirring temperature of the stirring modification treatment is 55-60° C., the stirring speed is 450-500 r / min, and the stirring time is 35-45 min.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] 1. The special adhesive for anti-deformation rock slabs of the present invention adopts quartz sand, cement, polymer adhesive powder, hydroxypropyl methylcellulose, and adds a carbon fiber hybridization-based conditioning agent and a metakaolin modifier. The two raw materials are blended and coordinated to enhance the synergy. The obtained special adhesive product has balanced and coordinated improvements in impact toughness, tensile strength performance and thermal conductivity, and the product has significant effects on resistance to cold and heat, acid corrosion and solvent stability.
[0029] 2. In the preparation of the carbon fiber hybridization agent, silicon carbide is prepared by mixing lanthanum chloride solution to prepare silicon carbide liquid, and then bauxite, nano silica sol and sodium citrate solution are fully blended to obtain bauxite agent, and the bauxite agent is mixed with the silicon carbide liquid to coordinate and enhance the performance coordination and stability of the system as a matrix material;
[0030] 3. The carbon fiber hybrid liquid added at the same time is improved by ball milling. The carbon fiber hybrid liquid is blended and coordinated with carbon fiber, cerium oxide, stearic acid, nano zirconium oxide and sodium dodecylbenzene sulfonate solution. Carbon fiber is used as a matrix agent. The carbon fiber has high strength, toughness and modulus, and can absorb stress and heat transfer, optimize the anti-falling and anti-deformation effects of the rubber product, thereby improving the performance coordination of the product, and the synergy of the matched raw materials such as nano zirconium oxide and cerium oxide further enhances the performance coordination and performance stability of the product;
[0031] 4. The kaolin modifier is made of nano zinc oxide and nano silicon nitride, which are compounded, calcined, and activated with potassium permanganate solution. The obtained nano composite additive is better coordinated with the silane coupling agent KH550 and dopamine hydrochloride solution, so as to better improve the kaolin. The coordination and synergy between the kaolin and the coupling compound solution are enhanced, and the coordination effect between the obtained kaolin modifier and the carbon fiber hybrid-based modifier is enhanced, and the system structure and system performance are further strengthened, so that the performance effect of the product is further improved. DETAILED DESCRIPTION
[0032] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0033] The special adhesive for anti-falling and anti-deformation rock plate containing high carbon fiber in this embodiment includes the following raw materials in parts by weight:
[0034] 60-70 parts of quartz sand, 30-35 parts of cement, 10-15 parts of carbon fiber hybridization-based conditioning agent, 5-8 parts of polymer rubber powder, 3-5 parts of hydroxypropyl methylcellulose, 4-7 parts of metakaolin modifier and 40-45 parts of water;
[0035] The preparation method of the special glue for rock slabs is as follows: weigh the above raw materials in parts by weight according to the ratio, and then mix the raw materials sufficiently to obtain the special glue for rock slabs of the present invention.
[0036] The special glue for anti-falling and anti-deformation rock slabs in this embodiment includes the following raw materials in parts by weight:
[0037] 65 parts of quartz sand, 32.5 parts of cement, 12.5 parts of carbon fiber hybrid-based conditioning agent, 6.5 parts of polymer rubber powder, 4 parts of hydroxypropyl methylcellulose, 5.5 parts of kaolin modifier and 42.5 parts of water.
[0038] The polymer powder of this embodiment is acrylic powder; the specification of quartz sand is 200 mesh; and the cement is silicate 42.5R cement.
[0039] The preparation method of the carbon fiber hybridization-based feed agent of this embodiment is as follows:
[0040] S01: first prepare a lanthanum chloride solution with a mass fraction of 2-5%, and then place silicon carbide in a lanthanum chloride solution with a mass fraction of 2-5% that is 3-5 times the total amount of silicon carbide, and stir and mix thoroughly to obtain silicon carbide liquid;
[0041] S02: 3 to 5 parts of bauxite, 1 to 3 parts of nano-silica sol and 2 to 4 parts of sodium citrate solution are mixed to obtain a bauxite agent;
[0042] S03: 5 to 8 parts of silicon carbide liquid and 2 to 4 parts of bauxite agent are mixed and ultrasonically treated. After the ultrasonic treatment is completed, the mixture is filtered and dried; heat treated at 150 to 160° C. for 10 to 15 minutes, and then air-cooled to room temperature to obtain a silicon carbide-bauxite body;
[0043] S04: The silicon carbide-bauxite body and the carbon fiber hybrid liquid are mixed in a weight ratio of 5:3 and ball-milled at a ball milling speed of 1000 r / min for 2 hours. After the ball milling is completed, the mixture is filtered and dried to obtain a carbon fiber hybrid-based adjusting agent.
[0044] The mass fraction of the sodium citrate solution in this embodiment is 6-8%; the ultrasonic power of the blending ultrasonic treatment is 350-400W, and the ultrasonic time is 20-30min.
[0045] The carbon fiber hybrid liquid of this embodiment includes the following raw materials in parts by weight:
[0046] 5 to 8 parts of carbon fiber, 2 to 3 parts of cerium oxide, 1 to 2 parts of stearic acid, 2 to 4 parts of nano zirconium oxide and 8 to 12 parts of sodium dodecylbenzene sulfonate solution.
[0047] The mass fraction of the sodium dodecylbenzenesulfonate solution in this embodiment is 3-5%.
[0048] The preparation method of the metakaolin modifier of this embodiment is:
[0049] S11: mixing nano zinc oxide and nano silicon nitride in a weight ratio of 3:2, and then calcining at 230-240° C. for 1-2 hours. After the calcination is completed, cooling to room temperature is performed to obtain a calcined material;
[0050] Then, the calcined material is added into a potassium permanganate solution which is 4 to 7 times the total amount of the calcined material, stirred and mixed thoroughly, and then washed with water, filtered and dried to obtain a nano composite additive;
[0051] S12: adding 3 to 5 parts of silane coupling agent KH550 and 1 to 3 parts of dopamine hydrochloride solution to 5 to 8 parts of ethanol solvent, and then adding 2 to 4 parts of nanocomposite additives and stirring to obtain a coupling compound solution;
[0052] S13: stirring and modifying the metakaolin and the coupling compound liquid in a weight ratio of 2:5, filtering and drying after the stirring is completed to obtain a metakaolin modifier.
[0053] The mass fraction of the dopamine hydrochloride solution in this embodiment is 5-8%; the mass fraction of the potassium permanganate solution is 3-6%.
[0054] The stirring temperature of the stirring modification treatment in this embodiment is 55-60° C., the stirring speed is 450-500 r / min, and the stirring time is 35-45 min.
[0055] Example 1.
[0056] The special adhesive for anti-falling and anti-deformation rock plate containing high carbon fiber in this embodiment includes the following raw materials in parts by weight:
[0057] 60 parts of quartz sand, 30 parts of cement, 10 parts of carbon fiber hybrid-based conditioning agent, 5 parts of polymer rubber powder, 3 parts of hydroxypropyl methylcellulose, 4 parts of metakaolin modifier and 40 parts of water;
[0058] The preparation method of the special glue for rock slabs is as follows: weigh the above raw materials in parts by weight according to the ratio, and then mix the raw materials sufficiently to obtain the special glue for rock slabs of the present invention.
[0059] The polymer powder of this embodiment is acrylic powder; the specification of quartz sand is 200 mesh; and the cement is silicate 42.5R cement.
[0060] The preparation method of the carbon fiber hybridization-based feed agent of this embodiment is as follows:
[0061] S01: first prepare a 2% by mass lanthanum chloride solution, then place silicon carbide in a 2% by mass lanthanum chloride solution that is 3 times the total amount of silicon carbide, and stir and mix thoroughly to obtain silicon carbide liquid;
[0062] S02: 3 parts of bauxite, 1 part of nano silica sol and 2 parts of sodium citrate solution are mixed to obtain a bauxite agent;
[0063] S03: 5 parts of silicon carbide liquid and 2 parts of bauxite agent are mixed and ultrasonically treated. After the ultrasonic treatment is finished, the mixture is filtered and dried. The mixture is heat treated at 150° C. for 10 minutes and then air-cooled to room temperature to obtain a silicon carbide-bauxite body.
[0064] S04: The silicon carbide-bauxite body and the carbon fiber hybrid liquid are mixed in a weight ratio of 5:3 and ball-milled at a ball milling speed of 1000 r / min for 2 hours. After the ball milling is completed, the mixture is filtered and dried to obtain a carbon fiber hybrid-based adjusting agent.
[0065] The mass fraction of the sodium citrate solution in this embodiment is 6%; the ultrasonic power of the blending ultrasonic treatment is 350W, and the ultrasonic time is 20min.
[0066] The carbon fiber hybrid liquid of this embodiment includes the following raw materials in parts by weight:
[0067] 5 parts of carbon fiber, 2 parts of cerium oxide, 1 part of stearic acid, 2 parts of nano zirconium oxide and 8 parts of sodium dodecylbenzene sulfonate solution.
[0068] The mass fraction of the sodium dodecylbenzenesulfonate solution in this embodiment is 3%.
[0069] The preparation method of the metakaolin modifier of this embodiment is:
[0070] S11: mixing nano zinc oxide and nano silicon nitride in a weight ratio of 3:2, and then calcining at 230° C. for 1 hour. After the calcination is completed, cooling to room temperature is performed to obtain a calcined material;
[0071] Then, the calcined material is added into a potassium permanganate solution of 4 times the total amount of the calcined material, stirred and mixed thoroughly, and then washed with water, filtered and dried to obtain a nano composite additive;
[0072] S12: adding 3 parts of silane coupling agent KH550 and 1 part of dopamine hydrochloride solution to 5 parts of ethanol solvent, and then adding 2 parts of nanocomposite additives and stirring to mix well to obtain a coupling compound solution;
[0073] S13: stirring and modifying the metakaolin and the coupling compound liquid in a weight ratio of 2:5, filtering and drying after the stirring is completed to obtain a metakaolin modifier.
[0074] The mass fraction of the dopamine hydrochloride solution in this embodiment is 5%; the mass fraction of the potassium permanganate solution is 3%.
[0075] The stirring temperature of the stirring modification treatment in this embodiment is 55° C., the stirring speed is 450 r / min, and the stirring time is 35 min.
[0076] Example 2.
[0077] The special adhesive for anti-falling and anti-deformation rock plate containing high carbon fiber in this embodiment includes the following raw materials in parts by weight:
[0078] 70 parts of quartz sand, 35 parts of cement, 15 parts of carbon fiber hybrid-based conditioning agent, 8 parts of polymer rubber powder, 5 parts of hydroxypropyl methylcellulose, 7 parts of metakaolin modifier and 45 parts of water;
[0079] The preparation method of the special glue for rock slabs is as follows: weigh the above raw materials in parts by weight according to the ratio, and then mix the raw materials sufficiently to obtain the special glue for rock slabs of the present invention.
[0080] The polymer powder of this embodiment is acrylic powder; the specification of quartz sand is 200 mesh; and the cement is silicate 42.5R cement.
[0081] The preparation method of the carbon fiber hybridization-based feed agent of this embodiment is as follows:
[0082] S01: first prepare a 5% by mass lanthanum chloride solution, then place silicon carbide in a 5% by mass lanthanum chloride solution that is 5 times the total amount of silicon carbide, and stir and mix thoroughly to obtain silicon carbide liquid;
[0083] S02: 5 parts of bauxite, 3 parts of nano silica sol and 4 parts of sodium citrate solution are fully mixed to obtain a bauxite agent;
[0084] S03: 8 parts of silicon carbide liquid and 4 parts of bauxite agent are mixed and ultrasonically treated. After the ultrasonic treatment is completed, the mixture is filtered and dried. The mixture is heat treated at 160° C. for 15 minutes and then air-cooled to room temperature to obtain a silicon carbide-bauxite body.
[0085] S04: The silicon carbide-bauxite body and the carbon fiber hybrid liquid are mixed in a weight ratio of 5:3 and ball-milled at a ball milling speed of 1000 r / min for 2 hours. After the ball milling is completed, the mixture is filtered and dried to obtain a carbon fiber hybrid-based adjusting agent.
[0086] The mass fraction of the sodium citrate solution in this embodiment is 8%; the ultrasonic power of the blending ultrasonic treatment is 400 W, and the ultrasonic time is 30 min.
[0087] The carbon fiber hybrid liquid of this embodiment includes the following raw materials in parts by weight:
[0088] 8 parts of carbon fiber, 3 parts of cerium oxide, 2 parts of stearic acid, 4 parts of nano zirconium oxide and 12 parts of sodium dodecylbenzene sulfonate solution.
[0089] The mass fraction of the sodium dodecylbenzenesulfonate solution in this embodiment is 5%.
[0090] The preparation method of the metakaolin modifier of this embodiment is:
[0091] S11: mixing nano zinc oxide and nano silicon nitride in a weight ratio of 3:2, and then calcining at 240° C. for 2 h. After the calcination is completed, cooling to room temperature is performed to obtain a calcined material;
[0092] Then, the calcined material is added into a potassium permanganate solution which is 7 times the total amount of the calcined material, stirred and mixed thoroughly, and then washed with water, filtered and dried to obtain a nano composite additive;
[0093] S12: adding 5 parts of silane coupling agent KH550 and 3 parts of dopamine hydrochloride solution to 8 parts of ethanol solvent, and then adding 4 parts of nanocomposite additives and stirring to obtain a coupling compound solution;
[0094] S13: stirring and modifying the metakaolin and the coupling compound liquid in a weight ratio of 2:5, filtering and drying after the stirring is completed to obtain a metakaolin modifier.
[0095] The mass fraction of the dopamine hydrochloride solution in this embodiment is 8%; the mass fraction of the potassium permanganate solution is 6%.
[0096] The stirring temperature of the stirring modification treatment in this embodiment is 60° C., the stirring speed is 500 r / min, and the stirring time is 45 min.
[0097] Example 3.
[0098] The special adhesive for anti-falling and anti-deformation rock plate containing high carbon fiber in this embodiment includes the following raw materials in parts by weight:
[0099] 65 parts of quartz sand, 32.5 parts of cement, 12.5 parts of carbon fiber hybrid-based conditioning agent, 6.5 parts of polymer rubber powder, 4 parts of hydroxypropyl methylcellulose, 5.5 parts of metakaolin modifier and 42.5 parts of water;
[0100] The preparation method of the special glue for rock slabs is as follows: weigh the above raw materials in parts by weight according to the ratio, and then mix the raw materials sufficiently to obtain the special glue for rock slabs of the present invention.
[0101] The polymer powder of this embodiment is acrylic powder; the specification of quartz sand is 200 mesh; and the cement is silicate 42.5R cement.
[0102] The preparation method of the carbon fiber hybridization-based feed agent of this embodiment is as follows:
[0103] S01: first prepare a 3.5% by mass lanthanum chloride solution, then place silicon carbide in a 3.5% by mass lanthanum chloride solution that is 4 times the total amount of silicon carbide, and stir and mix thoroughly to obtain silicon carbide liquid;
[0104] S02: 4 parts of bauxite, 2 parts of nano silica sol and 3 parts of sodium citrate solution are fully mixed to obtain a bauxite agent;
[0105] S03: 6.5 parts of silicon carbide liquid and 3 parts of bauxite agent are mixed and ultrasonically treated. After the ultrasonic treatment is completed, the mixture is filtered and dried. The mixture is heat treated at 155° C. for 12.5 min and then air-cooled to room temperature to obtain a silicon carbide-bauxite body.
[0106] S04: The silicon carbide-bauxite body and the carbon fiber hybrid liquid are mixed in a weight ratio of 5:3 and ball-milled at a ball milling speed of 1000 r / min for 2 hours. After the ball milling is completed, the mixture is filtered and dried to obtain a carbon fiber hybrid-based adjusting agent.
[0107] The mass fraction of the sodium citrate solution in this embodiment is 7%; the ultrasonic power of the blending ultrasonic treatment is 370W, and the ultrasonic time is 25min.
[0108] The carbon fiber hybrid liquid of this embodiment includes the following raw materials in parts by weight:
[0109] 6.5 parts of carbon fiber, 2.5 parts of cerium oxide, 1.5 parts of stearic acid, 3 parts of nano zirconium oxide and 10 parts of sodium dodecylbenzene sulfonate solution.
[0110] The mass fraction of the sodium dodecylbenzenesulfonate solution in this embodiment is 4%.
[0111] The preparation method of the metakaolin modifier of this embodiment is:
[0112] S11: mixing nano zinc oxide and nano silicon nitride in a weight ratio of 3:2, and then calcining at 235° C. for 1.5 h. After the calcination is completed, cooling to room temperature is performed to obtain a calcined material;
[0113] Then, the calcined material is added into a potassium permanganate solution which is 5.5 times the total amount of the calcined material, stirred and mixed thoroughly, and then washed with water, filtered and dried to obtain a nano composite additive;
[0114] S12: adding 4 parts of silane coupling agent KH550 and 2 parts of dopamine hydrochloride solution to 6.5 parts of ethanol solvent, and then adding 3 parts of nanocomposite additives and stirring to obtain a coupling compound solution;
[0115] S13: stirring and modifying the metakaolin and the coupling compound liquid in a weight ratio of 2:5, filtering and drying after the stirring is completed to obtain a metakaolin modifier.
[0116] The mass fraction of the dopamine hydrochloride solution in this embodiment is 6.5%; the mass fraction of the potassium permanganate solution is 4.5%.
[0117] The stirring temperature of the stirring modification treatment in this embodiment is 57.5° C., the stirring speed is 470 r / min, and the stirring time is 40 min.
[0118] Comparative Example 1.
[0119] The difference from Example 3 is that no carbon fiber hybridization agent is added.
[0120] Comparative Example 2.
[0121] The difference from Example 3 is that no silicon carbide-alumina body is added in the preparation of the carbon fiber hybridization conditioning agent.
[0122] Comparative Example 3.
[0123] The difference from Example 3 is that no silicon carbide liquid is added during the preparation of the silicon carbide-bauxite body.
[0124] Comparative Example 4.
[0125] The difference from Example 3 is that no bauxite agent is added in the preparation of the silicon carbide-bauxite body.
[0126] Comparative Example 5.
[0127] The difference from Example 3 is that no carbon fiber hybridization liquid is added in the preparation of the carbon fiber hybridization conditioning agent.
[0128] Comparative Example 6.
[0129] The difference from Example 3 is that no metakaolin modifier is added.
[0130] Comparative Example 7.
[0131] The difference from Example 3 is that no coupling rehydration liquid is added in the preparation of the metakaolin modifier.
[0132] Comparative Example 8.
[0133] The difference from Example 3 is that no nanocomposite additive is added to the coupling compounding solution.
[0134] Comparative Example 9.
[0135] The difference from Example 3 is that no nano silicon nitride is added in the preparation of the nano composite additive.
[0136] Comparative Example 10.
[0137] The difference from Example 3 is that nano zinc oxide is not added in the preparation of the nano composite additive.
[0138] Comparative Example 11.
[0139] The difference from Example 3 is that no silane coupling agent KH550 and dopamine hydrochloride solution are added to the coupling compounding solution.
[0140] Comparative Example 12.
[0141] The difference from Example 3 is that no metakaolin is added in the preparation of the metakaolin modifier.
[0142] The products of Examples 1 to 3 and Comparative Examples 1 to 12 were subjected to conventional performance tests, and the total crack area per unit area was tested with reference to the literature in CN115259782B. At the same time, the products were placed in 2% hydrochloric acid mist for 10 hours, and then placed in acetone solvent for 10 hours to test the acid resistance and solvent resistance stability of the products. The test results are as follows
[0143]
[0144]
[0145]
[0146] Based on the above acid and solvent resistance tests, the product was placed at 70°C for 24 hours to test its high temperature stability. The test results are as follows;
[0147]
[0148]
[0149] It can be seen from the tests under comparative examples 1-12 and embodiments 1-3 and acid resistance, solvent resistance and high temperature resistance conditions;
[0150] The product of Example 3 has excellent thermal conductivity, tensile strength, impact toughness and crack resistance, and the performance of the product can be improved in a coordinated manner, and the product has significant performance stability under acid resistance, solvent resistance and high temperature resistance conditions;
[0151] The present invention does not add a carbon fiber hybridization-based conditioning agent or a metakaolin modifier, and the performance stability of the product shows a significant trend of deterioration. The coordination and synergy of the two are adopted to achieve the most significant performance effect of the product.
[0152] In the preparation of the carbon fiber hybridization-based adjusting agent, no silicon carbide-bauxite body was added, no silicon carbide liquid was added in the preparation of the silicon carbide-bauxite body, no bauxite agent was added in the preparation of the silicon carbide-bauxite body, and no carbon fiber hybrid liquid was added in the preparation of the adjusting agent based on carbon fiber hybridization. The performance of the product has a trend of deterioration to varying degrees. At the same time, the performance of the product has a more obvious trend of deterioration when no carbon fiber hybrid liquid is added;
[0153] The performance effect of the product obtained by combining the silicon carbide-alumina body obtained by the specific method of the present invention with the carbon fiber hybrid liquid to obtain the carbon fiber hybridization-based conditioning agent is the most significant.
[0154] The performance of the products showed a trend of deterioration to varying degrees when no coupling compounding solution was added to the preparation of the metakaolin modifier, no nano-composite additive was added to the coupling compounding solution, no nano-silicon nitride was added to the preparation of the nano-composite additive, no nano-zinc oxide was added to the preparation of the nano-composite additive, no silane coupling agent KH550, no dopamine hydrochloride solution was added to the coupling compounding solution, and no metakaolin was added to the preparation of the metakaolin modifier;
[0155] The nanocomposite additive obtained by the method of the present invention is added to the coupling compounding solution, and then combined with the metakaolin modifier obtained by a specific process method, the product performance effect is the most significant, and other methods are not as obvious as the effect of the present invention.
[0156] Based on the above tests, the present invention further explores the product performance through the composition of the carbon fiber hybrid liquid;
[0157] The carbon fiber hybrid liquid includes the following raw materials in parts by weight:
[0158] 5 to 8 parts of carbon fiber, 2 to 3 parts of cerium oxide, 1 to 2 parts of stearic acid, 2 to 4 parts of nano zirconium oxide and 8 to 12 parts of sodium dodecylbenzene sulfonate solution.
[0159] Experimental example 1.
[0160] The only difference from Example 3 is that no carbon fiber is added to the carbon fiber hybrid liquid.
[0161] Experimental example 2.
[0162] The only difference from Example 3 is that cerium oxide is not added to the carbon fiber hybrid liquid.
[0163] Experimental Example 3.
[0164] The only difference from Example 3 is that nano zirconium oxide is not added to the carbon fiber hybrid liquid.
[0165] Experimental Example 4.
[0166] The only difference from Example 3 is that stearic acid is not added to the carbon fiber hybrid solution and the sodium dodecylbenzene sulfonate solution is replaced by water.
[0167] Taking the product under acid resistance, solvent resistance and high temperature resistance as an example, the performance test is carried out, and its performance is tested as follows;
[0168]
[0169] It can be seen from Experimental Examples 1-4 that carbon fiber is not added to the carbon fiber hybrid liquid, and the performance of the product changes. Among the components of the carbon fiber hybrid liquid, the performance deterioration is the most obvious, followed by the absence of nano zirconium oxide. At the same time, cerium oxide is not added to the carbon fiber hybrid liquid, stearic acid is not added to the carbon fiber hybrid liquid, and the sodium dodecylbenzene sulfonate solution is replaced by water. The performance of the product has a trend of deterioration to varying degrees. The carbon fiber hybrid liquid composed by the specific method of the present invention has the most significant performance effect of the product. At the same time, the composition of the carbon fiber hybrid liquid is proprietary, and the technical effect of the present invention cannot be achieved by replacing it with other methods.
[0170] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
[0171] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. Special adhesive for anti-falling and anti-deformation rock board containing high carbon fiber, characterized in that: It includes the following raw materials in parts by weight: 60-70 parts of quartz sand, 30-35 parts of cement, 10-15 parts of carbon fiber hybridization-based conditioning agent, 5-8 parts of polymer rubber powder, 3-5 parts of hydroxypropyl methylcellulose, 4-7 parts of metakaolin modifier and 40-45 parts of water; The preparation method of the special glue for rock slabs is as follows: weigh the above raw materials according to the weight ratio, and then mix the raw materials sufficiently to obtain the special glue for rock slabs; The preparation method of the carbon fiber hybridization-based conditioning agent is as follows: S01: first prepare a lanthanum chloride solution with a mass fraction of 2-5%, and then place silicon carbide in a lanthanum chloride solution with a mass fraction of 2-5% that is 3-5 times the total amount of silicon carbide, and stir and mix thoroughly to obtain silicon carbide liquid; S02: 3-5 parts of bauxite, 1-3 parts of nano-silica sol and 2-4 parts of sodium citrate solution are mixed to obtain a bauxite agent; S03: 5-8 parts of silicon carbide liquid and 2-4 parts of bauxite agent are mixed and ultrasonically treated, and after the ultrasonic treatment, the mixture is filtered and dried; heat treated at 150-160° C. for 10-15 minutes, and then air-cooled to room temperature to obtain a silicon carbide-bauxite body; S04: mixing the silicon carbide-alumina body and the carbon fiber hybrid liquid in a weight ratio of 5:3, ball milling at a ball milling speed of 1000 r / min, ball milling for 2 hours, filtering and drying after the ball milling is completed, to obtain a carbon fiber hybridizing agent; The carbon fiber hybrid liquid comprises the following raw materials in parts by weight: 5-8 parts of carbon fiber, 2-3 parts of cerium oxide, 1-2 parts of stearic acid, 2-4 parts of nano zirconium oxide and 8-12 parts of sodium dodecylbenzene sulfonate solution; The preparation method of the metakaolin modifier is: S11: mixing nano zinc oxide and nano silicon nitride in a weight ratio of 3:2, and then calcining at 230-240° C. for 1-2 hours. After the calcination is completed, cooling to room temperature is performed to obtain a calcined material; Then, the calcined material is added into a potassium permanganate solution which is 4 to 7 times the total amount of the calcined material, stirred and mixed thoroughly, and then washed with water, filtered and dried to obtain a nano composite additive; S12: adding 3-5 parts of silane coupling agent KH550 and 1-3 parts of dopamine hydrochloride solution to 5-8 parts of ethanol solvent, and then adding 2-4 parts of nanocomposite additives and stirring to obtain a coupling compound solution; S13: stirring and modifying the metakaolin and the coupling compound liquid in a weight ratio of 2:5, filtering and drying after the stirring is completed to obtain a metakaolin modifier.
2. The special adhesive for anti-falling and anti-deformation rock plate containing high carbon fiber according to claim 1 is characterized in that: The special glue for anti-falling and anti-deformation rock slabs includes the following raw materials in parts by weight: 65 parts of quartz sand, 32.5 parts of cement, 12.5 parts of carbon fiber hybrid-based conditioning agent, 6.5 parts of polymer rubber powder, 4 parts of hydroxypropyl methylcellulose, 5.5 parts of kaolin modifier and 42.5 parts of water.
3. The special adhesive for anti-falling and anti-deformation rock plate containing high carbon fiber according to claim 1, characterized in that: The polymer powder is acrylic powder; the specification of quartz sand is 200 mesh; and the cement is silicate 42.5R cement.
4. The special adhesive for anti-falling and anti-deformation rock plate containing high carbon fiber according to claim 1, characterized in that: The mass fraction of the sodium citrate solution is 6-8%; the ultrasonic power of the blended ultrasonic treatment is 350-400W, and the ultrasonic time is 20-30min.
5. The special adhesive for anti-falling and anti-deformation rock plate containing high carbon fiber according to claim 1, characterized in that: The mass fraction of the sodium dodecylbenzene sulfonate solution is 3-5%.
6. The special adhesive for anti-falling and anti-deformation rock plate containing high carbon fiber according to claim 1, characterized in that: The mass fraction of the dopamine hydrochloride solution is 5-8%; the mass fraction of the potassium permanganate solution is 3-6%.
7. The special adhesive for anti-falling and anti-deformation rock plate containing high carbon fiber according to claim 1, characterized in that: The stirring temperature of the stirring modification treatment is 55-60° C., the stirring speed is 450-500 r / min, and the stirring time is 35-45 min.
Citation Information
Patent Citations
A crack-resistant concrete and its construction method
CN115259782B
Carbon fiber ceramic tile pasting material, ceramic tile adhesive and application
CN117417156A
Adhesive for adhering large-size rock plate for polyurethane modified cement
CN117447138A